2022
DOI: 10.1021/accountsmr.1c00201
|View full text |Cite
|
Sign up to set email alerts
|

Defect Engineering in Photocatalysts and Photoelectrodes: From Small to Big

Abstract: Conspectus Green hydrogen as a clean energy carrier plays a critical role in tackling climate change. Solar-driven water splitting is regarded as one of the most promising strategies for green hydrogen production, but the solar-to-hydrogen (STH) conversion efficiency is still far from the industrial requirement. Defect engineering is an effective strategy to enhance the performance of photocatalysts and photoelectrodes. In a crystal, defects range from micro- to macro-levels, such as atomic-scale vacancies and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…To enhance the photocatalytic property of g-C 3 N 4 , various approaches have been proposed, e.g., doping, 52,53 obtaining porous architectures, 54,55 achieving highly crystalline structures, 56 metal loading, 57,58 heterojunction construction, [59][60][61] exfoliation, 62,63 defect engineering, 64,65 and molecular and electronic structure engineering. [66][67][68][69] Among these approaches, the integration of two semiconductors to fabricate type-II heterojunctions is a promising method for enhancing the photocatalytic performance since the band alignment between the two semiconductors will provide high separation efficiency of the photogenerated carrier.…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the photocatalytic property of g-C 3 N 4 , various approaches have been proposed, e.g., doping, 52,53 obtaining porous architectures, 54,55 achieving highly crystalline structures, 56 metal loading, 57,58 heterojunction construction, [59][60][61] exfoliation, 62,63 defect engineering, 64,65 and molecular and electronic structure engineering. [66][67][68][69] Among these approaches, the integration of two semiconductors to fabricate type-II heterojunctions is a promising method for enhancing the photocatalytic performance since the band alignment between the two semiconductors will provide high separation efficiency of the photogenerated carrier.…”
Section: Introductionmentioning
confidence: 99%
“…The photocatalytic activity of a nanomaterial can be influenced by shape and size architecting, ,,− surface passivation, − defect engineering, − doping, − and formation of heterojunctions. − The modulation of shape in the NCs and the generation of active facets or sites can increase the photocatalytic efficiency by accelerating the association followed by dissociation of reactants and products, respectively. Furthermore, tuning the active size of the materials can create an effective surface area.…”
Section: Introductionmentioning
confidence: 99%
“…To address these stringent requirements, one possible route consists in using hybrid metal–semiconductor nanostructures combining the former’s exceptional optical properties and the possibility of forming rectifying junctions. − Furthermore, the fabrication of properly designed hybrid nanosystems requires considerable effort in understanding both parts and, even more, their interfaces. For example, the optical properties of the nanostructures are linked directly to their size, shape, composition, and embedding media, while the generated charge carrier energy, lifetime, and availability for redox processes rely on their surface states (e.g., crystallinity, defects, etc..) and the metal–semiconductor interface as well as with the surrounding media status. − …”
Section: Introductionmentioning
confidence: 99%
“…Induced defects such as oxygen vacancies (V O s) and Ti 3+ states are well-known because of their simple formation process (e.g., thermal treatment in a reducing atmosphere) while significantly affecting the photocatalyst properties. − ,− For instance, Chen et al showed the narrowing of the TiO 2 optical band gap from 3.3 to 1.54 eV through lattice disorder, inducing defect states (DSs) stabilized by hydrogen atoms . The V O s, from which Ti 3+ states arise, introduced by thermal treatment under H 2 , correspond to defect levels 0.7–1 eV below the CB .…”
Section: Introductionmentioning
confidence: 99%